Sodium and calcium interactions in vascular smooth muscle cells of the rabbit ear artery (The Rockefeller University Press, 1979)
The effects of Na-free and of K-free solutions on the membrane potential, on tension development, and on 45Ca exchange have been investigated in rabbit ear artery. The contraction induced by Na-free solutions and the tension which develops in K-free solutions after a delay of about 1 h are both submaximal. Exposure for 4 h to K-free solutions does not affect the membrane potential, whereas Na-free solutions depolarize the cells by 10-20 mV, depending on the Na- substitute. Neither the amplitude nor the rate constant of the slowly exchanging 45Ca-fraction is affected by these experimental procedures. Substituting external Na by choline or TMA induces a transient increase of the 45Ca-efflux rate which does not occur in a Ca-free efflux medium, and which can be blocked with La. K readmission to Na-enriched tissues hyperpolarizes the cells up to -100 mV and induces a relaxation, without exerting any effect on the 45Ca efflux rate. The release of Ca from intracellular stores, induced by histamine and FCCP, and its subsequent extrusion through the plasma membrane produce a transient stimulation of the 45Ca efflux, which is not affected by the reduction of the Na gradient. The transient contraction induced by histamine in Ca-free solutions is affected in a different way by different Na substitutes. The results do not fit the Na-Ca exchange hypothesis but are consistent with an effect of the Na gradient on the passive Ca influx.